Effects of ascorbic acid and kelulut honey as antibrowning agent on the quality of minimally processed jackfruit (Artocarpus heterophyllus) - Hussain, Norhayati; Rajentran, Komati; Wan Mohd Zul, Wan Nur Amalin Syakira; Azhar, Najjah; Mohd Fuad, Nur Filza (Luminescience Press Limited, 2023)
Minimally processed jackfruit is gaining popularity for its economic importance to the fruit industry, but its high susceptibility to enzymatic browning has been its limitation. This study determines the effects of applying ascorbic acid (AA) and kelulut honey (KH) on the shelf life of minimally processed jackfruit (MPJ) stored at chill and ambient temperature for 12 days. The quality of treated and untreated minimally processed jackfruit was evaluated by weight loss, firmness, colour (L* and b*), ascorbic acid content and browning inhibition. A microbiological analysis was performed to estimate the shelf-life. The MPJs dipped in 3% ascorbic acid and 3% kelulut honey and stored at 4°C showed the least weight loss of 0.75% and 0.42%, respectively, and the significantly least reduction in firmness of 67.93% and 65.24%, respectively. Ascorbic acid was found to be more efficient in reducing the discolouration of MPJ compared to kelulut honey. Depending on the temperature, the 3% KH dipping solution is more efficient than ascorbic acid in inhibiting the browning activity of MPJ with an inhibition of 9.29%, retaining ascorbic acid content (16.45 mg/100 g) and inhibiting microbial growth (6.20 log CFU/g) of MPJ up to 9 days of storage.